Problem: Evaluate $$ L=\displaystyle \lim_{n \to \infty} \frac{1}{n} \sum_{k=1}^{n} \left( \left\lfloor \frac{2n}{k} \right\rfloor -2\left\lfloor \frac{n}{k}\right \rfloor \right).$$

Please help me with this one.

I tried using the sandwich theorem by first constructing the following $$ 2 \geq \left\lfloor \frac{2n}{k} \right\rfloor -2\left\lfloor \frac{n}{k} \right\rfloor \geq -1 $$ and then summing over. But the limit of the two bounds are different so sandwich theorem doesn't help!. Is it possible to construct sharper bounds?

Also I observed that if we ignore question of continuity, etc. then we can write,

$L= \displaystyle \int ^{1}_{0}\left\lfloor \frac{2}{x} \right\rfloor -2\left\lfloor \frac{1}{x} \right\rfloor dx$ Now I am able to compute the above integral. But is the above process correct? If then how can make it rigorous? Or if any other approach is possible, please tell.

  • 1
    $\begingroup$ In the integral representation of $L$ there should be no $n$. $\endgroup$ May 3 '16 at 9:18

With the change of variable $x=\frac{1}{z}$ we get:

$$ L = \int_{1}^{+\infty}\frac{\lfloor 2z\rfloor -2\lfloor z\rfloor}{z^2}\,dx =\sum_{k\geq 1}\int_{k+\frac{1}{2}}^{k+1}\frac{dz}{z^2}=\sum_{k\geq 1}\frac{2}{(2k+1)(2k+2)}$$ hence:

$$ L = 2\int_{0}^{1}\sum_{k\geq 1}\left(z^{2k}-z^{2k+1}\right)\,dz =\int_{0}^{1}\frac{2z^2}{1+z}\,dz=\color{red}{2\log 2-1}.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.